2012 45th Hawaii International Conference on System Sciences 2012
DOI: 10.1109/hicss.2012.103
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Decision Support Model to Assess Reviewers for Research Project Selection

Abstract: Reviewers play a significant role in research project selection, because their opinions will have great influence on the decision of the projects which will be funded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…To support specific phases for research project selection, a hybrid knowledge rule and genetic algorithm is suggested for research proposal grouping [10][11], and furthermore, an ontology based text mining method (OTMM) to cluster proposals is proposed for research project selection [12]. A group decision support method is offered to evaluate experts for research project selection [13], and an integrated decision support model to assess reviewers for research project selection [14]. A hybrid knowledge-based and modeling approach is offered to assign reviewers to proposals for research project selection [15], while a decision support approach is presented for assigning reviewers to grouped proposals, and genetic algorithm is employed to solve the assignment problem [16].…”
Section: Introductionmentioning
confidence: 99%
“…To support specific phases for research project selection, a hybrid knowledge rule and genetic algorithm is suggested for research proposal grouping [10][11], and furthermore, an ontology based text mining method (OTMM) to cluster proposals is proposed for research project selection [12]. A group decision support method is offered to evaluate experts for research project selection [13], and an integrated decision support model to assess reviewers for research project selection [14]. A hybrid knowledge-based and modeling approach is offered to assign reviewers to proposals for research project selection [15], while a decision support approach is presented for assigning reviewers to grouped proposals, and genetic algorithm is employed to solve the assignment problem [16].…”
Section: Introductionmentioning
confidence: 99%